Sustainability Communication by Patagonia for Green Economic Growth - Aditia, Rafinita; Trung, Phan Nhan; Alfisyahri, Nuriah (Departemen Ilmu Komunikasi FISIP Universitas Atma Jaya Yogyakarta, 2025)
Abstract: This study examines how Patagonia's